Empowering Education: Cloud Solutions for Remote Schools in Indonesia - Ahmad, Asiyah (PT. Lentera Ilmu Publisher, 2024)
This article explores the transformative potential of cloud solutions in addressing the educational challenges faced by remote and underserved regions in Indonesia. The introduction highlights the significance of technology integration in education and emphasizes the obstacles Indonesia encounters in delivering quality education to remote areas. Cloud solutions emerge as a promising avenue, providing scalable tools to bridge the urban-rural learning gap. The literature review delves into the transformative impact of cloud-based education, citing studies that emphasize enhanced student engagement and personalized learning experiences. It underscores the importance of factors such as infrastructure development, internet connectivity, and digital literacy, essential for the success of cloud-based education in remote areas. Cultural considerations are also discussed, emphasizing the need to align technology with local values. The methodology section outlines the research steps, including a literature review, real-world implementation examples, exploration of potential benefits, and practical suggestions for policymakers and educators. Real examples of successful cloud technology implementations illustrate the positive outcomes, ranging from improved access to educational resources to streamlined administrative processes. The author summarizes the potential of cloud solutions, highlighting aspects such as accessibility, scalability, cost-effectiveness, collaboration, and personalized learning.